Penerapan Teknologi Tepat Guna Pembangkita Listrik Tenaga Mikro Hydro Di Desa Bangkit Rahmat Jailolo Selatan - Rais, Sandy; Tjiroso, Bambang (Patria Artha Journal of Community (PKM), 2021)
The potential use of renewable energy in Bangkit Rahmat Village from the results of a Kubermas student survey is there are 3 points of water sources that can be used as Micro Hydro power plants. From these three water sources, the location selected according to several aspects, including: Location or closest distance to residential areas, water discharge and head height, availability of technology application data, sustainability or MHP maintenance. The selection of the location for the implementation of the PLTMH implementation is in Hamlet II which is close to the source of the waterfall. The implementation of the MHP is carried out in several stages, including: making a reservoir, installing pipe installations and testing the power generated by the turbine using 3 LED lights. For the measurement of the water discharge, it was obtained 0.039 m3/second, the water head height was 2.5 meters and the water height hitting the blade of the wheel was 0.7 meters. From the results of testing the rotation on the wheel obtained is 70 rpm. With an efficiency of 57.07%, the hydraulic power produced by the windmill is 469.26 W. From the results of the calculations, the test, the turbine applied can use a generator with a capacity of up to 12 Kilo Watts, but as a material for the initial stages of implementation of the trial service, the generator used will be used is a generator with a capacity of 3 Kilo Watt.  Keywords: Microhydro power plant, Kubermas UNKHAIR, Bangkit Rahmat Village.